Laser-driven radioisotopes production at SCAPA for medical and industrial application. (December 2020) - Battaglia, G; Brunetti, E; Chishti, M M R; Lorusso, G; O'Donnell, D; Scheck, M; Wiggins, S M; Jaroszynski, D A
Abstract: Isotopes for nuclear medicine are scarce and expensive. Researchers worldwide are exploring new production methods to avoid the dependence on nuclear reactors as sources to satisfy future isotope demands. Photo-nuclear reactions have hitherto been used as a tool for studying the nuclear structure. Laser wakefield accelerators (LWFAs) are very compact accelerators capable of producing high energy electron beams. In this paper we investigate the possibility of using LWFAs to produce 225 Ac via photo-spallation reactions.